Acute leukoencephalopathy with restricted diffusion associated with Japanese encephalitis virus - Leema Pauline Cornelius; Asir Julin Paulraj; Neeraj Elango (Wolters Kluwer Medknow Publications, 2021)
Acute leukoencephalopathy with restricted diffusion (ALERD) is a clinicoradiological syndrome characterized by acute encephalopathy, seizures, and diffuse areas of restricted diffusion in bilateral cerebral parenchyma on magnetic resonance imaging. ALERD can occur following infections and exposure to drugs and toxins. Early recognition by neuroimaging and the institution of immunotherapy may be useful in improving neurological outcomes. We report a case of diffuse infectious ALERD associated with Japanese B encephalitis viral infection.